2016
DOI: 10.1136/sextrans-2015-052463
|View full text |Cite
|
Sign up to set email alerts
|

Gender-based violence against female sex workers in Cameroon: prevalence and associations with sexual HIV risk and access to health services and justice

Abstract: Among FSWs in Cameroon, violence is prevalent and undermines HIV prevention and access to healthcare and justice. Violence is highly relevant to FSWs' ability to successfully negotiate condom use and engage in healthcare. In this setting of criminalised sex work, an integrated, multisectoral GBV-HIV strategy that attends to structural risk is needed to enhance safety, HIV prevention and access to care and justice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
68
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 21 publications
6
68
0
Order By: Relevance
“…Gender-based violence (GBV) is common among sex workers [32]. In a systematic review of literature from Uganda, >80% of sex workers reported client-perpetrated violence while 18% experienced intimate partner violence.…”
Section: Discussionmentioning
confidence: 99%
“…Gender-based violence (GBV) is common among sex workers [32]. In a systematic review of literature from Uganda, >80% of sex workers reported client-perpetrated violence while 18% experienced intimate partner violence.…”
Section: Discussionmentioning
confidence: 99%
“…14,31 Stigma reduction, specifically among MSM and FSW has been shown in few settings. Reported perceived stigma, measured as fear of seeking health services, and avoiding health services, declined from baseline among participants in the longitudinal cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Targets Indicators Related Survey Questions The survey was adapted from studies with FSW across sub-Saharan Africa [16,[33][34][35][36][37] and pre-tested with FSW community members to ensure that questions were understood in English and Sesotho. Topics included socio-demographic characteristics, human rights violations, sexual behaviour, health service access, mental health, social capital, and reproductive health.…”
Section: Goalsmentioning
confidence: 99%